Optimization of solution-processed oligothiophene:fullerene based organic solar cells by using solvent additives - Schulz, Gisela L.; Urdanpilleta, Marta; Fitzner, Roland; Brier, Eduard; Mena-Osteritz, Elena; Reinold, Egon; Bäuerle, Peter (Beilstein Journal of Nanotechnology, 2013)
The optimization of solution-processed organic bulk-heterojunction solar cells with the acceptor-substituted quinquethiophene DCV5T-Bu4 as donor in conjunction with PC61BM as acceptor is described. Power conversion efficiencies up to 3.0% and external quantum efficiencies up to 40% were obtained through the use of 1-chloronaphthalene as solvent additive in the fabrication of the photovoltaic devices. Furthermore, atomic force microscopy investigations of the photoactive layer gave insight into the distribution of donor and acceptor within the blend. The unique combination of solubility and thermal stability of DCV5T-Bu4 also allows for fabrication of organic solar cells by vacuum deposition. Thus, we were able to perform a rare comparison of the device characteristics of the solution-processed DCV5T-Bu4:PC61BM solar cell with its vacuum-processed DCV5T-Bu4:C60 counterpart. Interestingly in this case, the efficiencies of the small-molecule organic solar cells prepared by using solution techniques are approaching those fabricated by using vacuum technology. This result is significant as vacuum-processed devices typically display much better performances in photovoltaic cells.
Keywords: active layer morphology; comparison vacuum-processed solar cells; maximum solubility; oligothiophene; solar cells; solution-processed bulk heterojunction; solvent additives

(untitled) - Spanggaard, H.; Krebs, F. C. (Sol. Energy Mater. Sol. Cells, 2004)

(untitled) - Günes, S.; Neugebauer, H.; Sariciftci, N. S. (Chem. Rev., 2007)

(untitled) - Boudreault, P.-L.; Najari, A.; Leclerc, M. (Chem. Mater., 2011)

(untitled) - Walker, B.; Kim, C.; Nguyen, T.-Q. (Chem. Mater., 2010)

(untitled) - Mishra, A.; Bäuerle, P. (Angew. Chem., Int. Ed., 2012)

(untitled) - Bürckstümmer, H.; Tulyakova, E. V.; Deppisch, M.; Lenze, M. R.; Kronenberg, N. M.; Gsänger, M.; Stolte, M.; Meerholz, K.; Würthner, F. (Angew. Chem., Int. Ed., 2011)

(untitled) - Xue, J.; Rand, B. P.; Uchida, S.; Forrest, S. R. (Adv. Mater., 2005)

(untitled) - Chen, G.; Sasabe, H.; Wang, Z.; Wang, X.-F.; Hong, Z.; Yang, Y.; Kido, J. (Adv. Mater., 2012)

(untitled) - Xiao, X.; Wei, G.; Wang, S.; Zimmerman, J. D.; Renshaw, C. K.; Thompson, M. E.; Forrest, S. R. (Adv. Mater., 2012)

(untitled) - Fitzner, R.; Mena-Osteritz, E.; Mishra, A.; Schulz, G.; Reinold, E.; Weil, M.; Körner, C.; Ziehlke, H.; Elschner, C.; Leo, K.; Riede, M.; Pfeiffer, M.; et al. (J. Am. Chem. Soc., 2012)

(untitled) - Wang, D. H.; Kyaw, A. K. K.; Gupta, V.; Bazan, G. C.; Heeger, A. J. (Adv. Energy Mater., 2013)

(untitled) - Yin, B.; Yang, L. Y.; Liu, Y. S.; Chen, Y. S.; Qi, Q. J.; Zhang, F. L.; Yin, S. G. (Appl. Phys. Lett., 2010)

(untitled) - Li, Z.; He, G.; Wan, X.; Liu, Y.; Zhou, J.; Long, G.; Zuo, Y.; Zhang, M.; Chen, Y. (Adv. Energy Mater., 2012)

(untitled) - Zhou, J.; Zuo, Y.; Wan, X.; Long, G.; Zhang, Q.; Ni, W.; Liu, Y.; Li, Z.; He, G.; Li, C.; Kan, B.; Li, M.; et al. (J. Am. Chem. Soc., 2013)

(untitled) - Zhou, J.; Wan, X.; Liu, Y.; Zuo, Y.; Li, Z.; He, G.; Long, G.; Ni, W.; Li, C.; Su, X.; Chen, Y. (J. Am. Chem. Soc., 2012)

(untitled) - Sun, Y.; Welch, G. C.; Leong, W. L.; Takacs, C. J.; Bazan, G. C.; Heeger, A. J. (Nat. Mater., 2012)

(untitled) - van der Poll, T. S.; Love, J. A.; Nguyen, T.-Q.; Bazan, G. C. (Adv. Mater., 2012)

(untitled) - Schulze, K.; Riede, M.; Brier, E.; Reinold, E.; Bäuerle, P.; Leo, K. (J. Appl. Phys., 2008)

(untitled) - Ziehlke, H.; Burtone, L.; Koerner, C.; Fitzner, R.; Reinold, E.; Bäuerle, P.; Leo, K.; Riede, M. (Org. Electron., 2011)

(untitled) - Schulze, K.; Uhrich, C.; Schüppel, R.; Leo, K.; Pfeiffer, M.; Brier, E.; Reinold, E.; Bäuerle, P. (Adv. Mater., 2006)

(untitled) - Haid, S.; Mishra, A.; Uhrich, C.; Pfeiffer, M.; Bäuerle, P. (Chem. Mater., 2011)

(untitled) - Chu, T.-Y.; Lu, J.; Beaupré, S.; Zhang, Y.; Pouliot, J.-R.; Wakim, S.; Zhou, J.; Leclerc, M.; Li, Z.; Ding, J.; Tao, Y. (J. Am. Chem. Soc., 2011)

(untitled) - Chen, H.-Y.; Yang, H.; Yang, G.; Sista, S.; Zadoyan, R.; Li, G.; Yang, Y. (J. Phys. Chem. C, 2009)

(untitled) - Yao, Y.; Hou, J.; Xu, Z.; Li, G.; Yang, Y. (Adv. Funct. Mater., 2008)

(untitled) - Salim, T.; Wong, L. H.; Bräuer, B.; Kukreja, R.; Foo, Y. L.; Bao, Z.; Lam, Y. M. (J. Mater. Chem., 2011)

(untitled) - Chen, F.-C.; Tseng, H.-C.; Ko, C.-J. (Appl. Phys. Lett., 2008)

(untitled) - Lee, J. K.; Ma, W. L.; Brabec, C. J.; Yuen, J.; Moon, J. S.; Kim, J. Y.; Lee, K.; Bazan, G. C.; Heeger, A. J. (J. Am. Chem. Soc., 2008)

(untitled) - Peet, J.; Kim, J. Y.; Coates, N. E.; Ma, W. L.; Moses, D.; Heeger, A. J.; Bazan, G. C. (Nat. Mater., 2007)

(untitled) - Graham, K. R.; Wieruszewski, P. M.; Stalder, R.; Hartel, M. J.; Mei, J.; So, F.; Reynolds, J. R. (Adv. Funct. Mater., 2012)

(untitled) - Adamopoulos, G.; Heiser, T.; Giovanella, U.; Ould-Saad, S.; van de Wetering, K. I.; Brochon, C.; Zorba, T.; Paraskevopoulos, K. M.; Hadziioannou, G. (Thin Solid Films, 2006)

(untitled) - Fuhrmann, G.; Krömer, J.; Bäurele, P. (Synth. Met., 2001)

(untitled) - Fitzner, R.; Reinold, E.; Mishra, A.; Mena-Osteritz, E.; Ziehlke, H.; Körner, C.; Leo, K.; Riede, M.; Weil, M.; Tsaryova, O.; Weiß, A.; Uhrich, C.; et al. (Adv. Funct. Mater., 2011)

(untitled) - Schulz, G. L.; Mastalerz, M.; Ma, C.-Q.; Wienk, M.; Janssen, R.; Bäuerle, P. (Macromolecules, 2013)

(untitled) - Lenes, M.; Wetzelaer, G.-J. A. H.; Kooistra, F. B.; Veenstra, S. C.; Hummelen, J. C.; Blom, P. W. M. (Adv. Mater., 2008)

(untitled) - Hummelen, J. C.; Knight, B. W.; LePeq, F.; Wudl, F.; Yao, J.; Wilkins, C. L. (J. Org. Chem., 1995)

(untitled) - Koster, L. J. A.; Mihailetchi, V. D.; Blom, P. W. M. (Appl. Phys. Lett., 2006)

(untitled) - Scharber, M. C.; Mühlbacher, D.; Koppe, M.; Denk, P.; Waldauf, C.; Heeger, A. J.; Brabec, C. J. (Adv. Mater., 2006)

(untitled) - Bijleveld, J. C.; Shahid, M.; Gilot, J.; Wienk, M. M.; Janssen, R. A. J. (Adv. Funct. Mater., 2009)

(untitled) - Shrotriya, V.; Yao, Y.; Li, G.; Yang, Y. (Appl. Phys. Lett., 2006)

(untitled) - Troshin, P. A.; Hoppe, H.; Renz, J.; Egginger, M.; Mayorova, J. Y.; Goryachev, A. E.; Peregudov, A. S.; Lyubovskaya, R. N.; Gobsch, G.; Sariciftci, N. S.; Razumov, V. F. (Adv. Funct. Mater., 2009)

(untitled) - Wynands, D.; Levichkova, M.; Leo, K.; Uhrich, C.; Schwartz, G.; Hildebrandt, D.; Pfeiffer, M.; Riede, M. (Appl. Phys. Lett., 2010)

(untitled) - Brabec, C. J.; Heeney, M.; McCulloch, I.; Nelson, J. (Chem. Soc. Rev., 2011)

(untitled) - Kronenberg, N. M.; Steinmann, V.; Bürckstümmer, H.; Hwang, J.; Hertel, D.; Würthner, F.; Meerholz, K. (Adv. Mater., 2010)

(untitled) - Wei, G.; Wang, S.; Renshaw, K.; Thompson, M. E.; Forrest, S. R. (ACS Nano, 2010)